Hierarchical pore structure based on cellulose nanofiber/melamine composite foam with enhanced sound absorption performance. (1st March 2021) - Shen, Lu; Zhang, Haoruo; Lei, Yanzhou; Chen, Yang; Liang, Mei; Zou, Huawei
Graphical abstract: Highlights: Cellulose nanofiber was combined with melamine foam by cyclic freezing-thawing. The constructed hierarchical pore structure includes macropores and mesopores. The complex pore structure enhanced the sound absorption over a broadband range. The prepared composite foam has enhanced mechanical property. The noise reduction coefficient of composite foam has an improvement of 80 %. Abstract: For the preparation of high-performance sound absorption materials, the fabrication of hierarchical pore structure has proven to be an effective way. Herein, cellulose nanofiber (CNF) and melamine foam (MF) were combined by an environmentally friendly method for the first time, which endowed the final composite foam with both macropores and mesopores. The hierarchical pore structure was constructed by cyclic freezing-thawing, which enhanced the multiple reflections and micro-vibration of the sound waves, resulting in an obvious improvement in sound absorption performance. Specifically, compared with the unmodified MF, the sound absorption performance of composite foam with a thickness of 20 mm at 0.4 wt% CNF concentration showed an enhancement of about 107 % at 500 Hz and the NRC (noise reduction coefficient) had an improvement of 80 %. This work is expected to provide more inspiration for the design and preparation of high-performance sound absorption materials.